Fault tolerance in wireless sensor networks with a multi-sink protocol and data confidence attribution - Scheffel, Roberto Milton (2021)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Ciência da Computação, Florianópolis, 2021.